2010
DOI: 10.1007/s00066-010-2131-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of VEGF and VEGF Receptor 1 (FLT1) Expression in Patients Irradiated for Stage II/III Non-Small Cell Lung Cancer (NSCLC)

Abstract: Tumor expression of VEGF and FLT1 appear to have no significant impact on LC, MFS, or OS in patients irradiated for NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The study of Checinska et al ( 41 ) suggested that caspase-9 may initiate a scaffold function and may serve as caspase substrate during NSCLC apoptosis. Additionally, therapy that targets VEGF has been demonstrated to be beneficial for the treatment of NSCLC ( 42 , 43 ). Furthermore, TRAIL-I-131 treatment markedly inhibited VEGF and AP-1 expression in A549 and H358 cells, which potentially contributed to the inhibitory efficacy of TRAIL-I-131 treatment for tumor growth in the NSCLC-bearing mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Checinska et al ( 41 ) suggested that caspase-9 may initiate a scaffold function and may serve as caspase substrate during NSCLC apoptosis. Additionally, therapy that targets VEGF has been demonstrated to be beneficial for the treatment of NSCLC ( 42 , 43 ). Furthermore, TRAIL-I-131 treatment markedly inhibited VEGF and AP-1 expression in A549 and H358 cells, which potentially contributed to the inhibitory efficacy of TRAIL-I-131 treatment for tumor growth in the NSCLC-bearing mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Whether methods which can be applied in the clinic can predict outcome after radiotherapy in patients, e.g., the gH2AX foci assay to estimate intrinsic radiosensitivity [7,10], specific surface markers to assess the number of tumor stem cells [2,9], and endogenous hypoxia markers [3,6,12], requires further validation.…”
Section: Tumormentioning
confidence: 99%
“…In response to the reduced O 2 availability, adaptative mechanisms such as increased glycolysis, glucose uptake, and survival factors, including HIFs and VEGF, are induced. These factors have miscellaneous effects on tumor progression and outcome of chemo-/ radiotherapy [2,13,15] .…”
Section: Introductionmentioning
confidence: 99%